2023
DOI: 10.1007/s41781-023-00094-w
|View full text |Cite
|
Sign up to set email alerts
|

The Tracking Machine Learning Challenge: Throughput Phase

Abstract: This paper reports on the second “Throughput” phase of the Tracking Machine Learning (TrackML) challenge on the Codalab platform. As in the first “Accuracy” phase, the participants had to solve a difficult experimental problem linked to tracking accurately the trajectory of particles as e.g. created at the Large Hadron Collider (LHC): given $$O(10^5)$$ O ( 10 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A Common Tracking Software (ACTS) [1] is a tracking framework being developed since 2016 as an international collaboration with the goal of providing a generic, experimentindependent open-source software framework for charged particle tracks reconstruction. To facilitate comprehensive research, ACTS offers two simulated detector geometries: the Generic Detector as shown in figure 1 is a standard all-silicon LHC-type tracking detector used in the TrackML [2] challenge and the Open Data Detector (ODD) [3], an evolved version of Generic Detector implemented using DD4Hep [4] that provides the support structure and the material akin to a real detector. The Generic detector has been used for the seeding and vertexing optimization studies while ODD has been used for the material mapping studies in this paper.…”
Section: Acts and Datasetmentioning
confidence: 99%
“…A Common Tracking Software (ACTS) [1] is a tracking framework being developed since 2016 as an international collaboration with the goal of providing a generic, experimentindependent open-source software framework for charged particle tracks reconstruction. To facilitate comprehensive research, ACTS offers two simulated detector geometries: the Generic Detector as shown in figure 1 is a standard all-silicon LHC-type tracking detector used in the TrackML [2] challenge and the Open Data Detector (ODD) [3], an evolved version of Generic Detector implemented using DD4Hep [4] that provides the support structure and the material akin to a real detector. The Generic detector has been used for the seeding and vertexing optimization studies while ODD has been used for the material mapping studies in this paper.…”
Section: Acts and Datasetmentioning
confidence: 99%
“…This study is performed using the TrackML dataset [4,5] that simulates the worst-case HL-LHC pileup conditions (⟨µ⟩ = 200) in a generic tracking detector geometry 1 . Our studies are limited to the innermost pixel detector layers, including 4 barrel layers and 7 layers in each endcap.…”
Section: Dataset and Input Featuresmentioning
confidence: 99%
“…This was done in the hope of finding novel, high performing, and fast methods that could boost the field. The challenge was divided into two parts, an accuracy part in which the performance accuracy of the submitted algorithms was assessed (Amrouche et al, 2020), and a throughput part in which the speed of the methods was evaluated (Amrouche et al, 2023). The accuracy phase resulted in the submission of many ML methods, which were considered highly innovative in the field (Amrouche et al, 2020).…”
Section: Benchmarks In Sciencementioning
confidence: 99%
“…The accuracy phase resulted in the submission of many ML methods, which were considered highly innovative in the field (Amrouche et al, 2020). In the throughput phase, the three top-ranked submissions in terms of speed were shown to be considerably faster than the state-of-the-art algorithms in the field at the time (Amrouche et al, 2023).…”
Section: Benchmarks In Sciencementioning
confidence: 99%
See 1 more Smart Citation